EFEKTIVITAS ATLAS ELEKTRONIK BERMUATAN KEANEKARAGAMAN TUMBUHAN TNBBS DALAM PEMBELAJARAN BIOLOGI BERDIFERENSIASI - Wiono, Wisnu Juli; Priadi, Median Agus; Meriza, Nadya (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
Bukit Barisan Selatan National Park (TNBBS) since 2004 has been named a Sumatran rainforest heritage by UNICEF. Several problems related to conservation efforts in TNBBS include decreasing area size, wood theft, and catching protected fauna. This condition has caused the TNBBS area to currently be in endangered (threatened) status. As an institution that plays a role in producing the nation's generation, schools have an important role in promoting environmental conservation efforts in learning activities. One form of business that can be done is to create learning materials that are effective, efficient, and contain plant biological resources in TNBBS. This research aims to produce an electronic atlas that can be used as a learning resource for students in biology subjects at the secondary education level. The research method applied was Thiagarajan's (1974) 4D development model (define, design, develop, and disseminate). The results of product validation by media experts are in the very feasible category. Meanwhile, material experts and field practitioners stated that it was feasible. The effectiveness test based on students' learning capital tendencies obtained data: visual (high); auditory (moderate); and kinesthetic (low). Based on the research results, the atlas containing the plant diversity of TNBBS is suitable for use in learning in the Merdeka Belajar curriculum.